KONTEKSTUALISASI ILMU AL- JARH WA AT-TA'DIL DALAM UPAYA MEMILIH WAKIL RAKYAT DAN KORELASINYA DENGAN TEORI KREDIBILITAS - Muhammad Qomarullah (Diroyah : Jurnal Studi Ilmu Hadis, 2019)
The election of representatives of the people as legislative candidates needs to used a method of criticism of the personality of leadership. In Islam this method is explicitly in the knowledge of hadith, namely the Jarah wa Ta'dil lesson, although this knowledge is only to criticize the credibility of the hadith narrators. But, to determine the personality of the people's representatives, true knowledge of rawi criticism can be used to elect leaders or representatives of the people. So, Credibility Theory as an addition is also very important to make the theory of meaning become meaningful to determine the prospective legislative candidates that will soon be implemented in Indonesia.